ANALISIS VARIASI JUMLAH ANTENA TERHADAP UNJUK KERJA SISTEM ORTHOGONAL FREQUENCY DIVISION MULTIPLEXING (OFDM) MULTIPLE INPUT MULTIPLE OUTPUT (MIMO) - Hakim, Muhammad Iman Nur; Wirastuti, Ni Made Ary Esta Dewi; Pramaita, Nyoman (Journal of Energy and Electrical Engineering, 2022)
OFDM is a transmission technique using orthogonal multi-carrier which can save bandwidth. While MIMO is a technique of using more than one antenna for transmitting and receiving. This can increase data transmission capacity without increasing bandwidth. In this study, an analysis of variations MIMO antennas 2x2, 2x4, 4x2, and 4x4 was carried out to determine the effect of antenna variations on OFDM MIMO performance. The modulation are BPSK and QPSK with frequency selective fading and AWGN channels. Performance parameters are Bit error rate (BER) versus Energy Bit per Noise (Eb/No), Power to Average Peak Ratio (PAPR), and eye diagram. The model simulated using a simulink with a number of input 100,000 bits. The results showed that BER performance compared to Eb/No, in MIMO 2x4 and 4x4 produced better performance than MIMO 2x2 and 4x2. With many receiving antennas, it gets a better signal which can reduce the occurrence of errors. Meanwhile, in PAPR parameter, 4x2 and 4x4 MIMO produce higher PAPR values than 2x2 and 2x4 MIMO. With the number of antennas, the PAPR value is distributed over all antennas and increase the PAPR value in the system. In the eye diagram parameters, the greater the Eb/No value, make a better eye diagram.